Teacher Implementation in the Mumtaz Smart Application during the Covid-19 Pandemic in Elementary Schools: Implementasi Guru dalam Aplikasi Mumtaz Smart dimasa Pandemi Covid-19 di Sekolah Dasar - Nugrahaningrum, Ratih; Wati, Tri Linggo (Indonesian Journal of Education Methods Development, 2022)
This research was conducted because there was a problem with online learning during the covid 19 pandemic to find out the implementation of teachers in the Mumtaz Smart application during the 5c covid 19 pandemic at SD Muhammadiyah 1 Taman. This research used a qualitative approach that aims to understand the phenomena experienced by researchers by collecting data through Observations, interviews and documentation were then checked for correctness through triangulation of data sources. The data obtained were analyzed using data reduction techniques, presenting data and drawing conclusions. The results of this study indicate that the implementation of teachers in online learning activities during the COVID-19 pandemic is going well where there is availability of media-based learning. digital learning process for the KBM process called the Mumtaz Smart application for daily learning activities the teacher always makes learning plans, implementation of learning and assessment of learning, but in this learning activity there are also obstacles faced by students, student guardians and teachers Keywords: Online learning, Covid-19, SD Muhammadiyah 1 Taman